Analysis Security, Location, and Word of Mouth of the Purchase Decision for Pantai Indah Kapuk 2 Housing - Amzad Samudro; Hamdan Hamdan (Dinasti International Journal of Management Science, 2023)
This study aims to determine the effect of security, location, and word of mouth on the purchasing decisions of respondents who are the owners of the Pantai Indah Kapuk 2 housing. This research is descriptive in nature. Primary data and secondary data obtained. Secondary data was obtained from various sources such as journalists, books and other related primary publication data obtained by distributing questionnaires to the target respondents. Determining the number of samples using purposive sampling technique and will be distributed via Google form to at least 160 respondents obtained. The results of primary data collection will be analyzed using the SEM-PLS method. The results of this study are that security, location, and word of mouth have a significant effect on the decision to purchase the Pantai Indah Kapuk 2 housing.